PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK LAYANAN, DAN HARGA PRODUK LAYANAN TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA TERHADAP LOYALITAS PELANGGAN PRABAYAR TELKOMSEL - Dwi Mulyono Nugroho (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract. Cellular telecommunications industry in Indonesia is growing veryrapidly with marked by fierce competition among cellular service providers inwhich it makes any business players in the mobile telecommunications industrytrying to maintain customers and get to reach new customers in order to ensure thesurvival of the company. This research aimed to determine the effect of servicequality, product quality and product pricing to customer satisfaction of prepaidTelkomsel products, which further acknowledge of customer satisfaction effect oncustomer loyalty prepaid Telkomsel products. Data collected by the deploymentof 220 (two hundred and twenty) questionnaire in the area of Jakarta are selectedby random sampling. The data obtained were processed through modelingStructural Equation Modeling (SEM) with the LISREL 8.7 applications and beprocessed using SPSS with the result that the quality of service and productquality give affected on customer satisfaction, product pricing does not affectedthe customer satisfaction and customer satisfaction affected on loyalty customers.The conclusion of this research is to increase customer satisfaction and loyalty,the company should giving more attention to activities related to improving thequality of service and product quality.Keywords: service quality, product quality, product pricing, customer satisfactionand customer loyalty.